Temporal Processing and Speech Perception Performance in Postlingual Adult Users of Cochlear Implants - CESUR, SIDIKA (AMER ACAD AUDIOLOGY, 2020)
Background: Cochlear implant (CI) listeners had some hearing problems, including catching clues from speech context, persist, particularly in complex listening environments. Among these hearing problems, temporal resolution is considered to be one of the most affected aspects of hearing. Purpose: The aim of the study is to assess and compare the temporal resolution ability of CI users and individuals with normal hearing using the Gaps-in-Noise (GIN) test. This study also aims to investigate whether there are any differences in speech recognition and temporal resolution performance between groups separated according to the implanted ear, gender, CI type, or sound processor strategies. Research Design: Case-control study. Study Samples: 18 adults (9 males, 9 females) with normal hearing, ranging in age between 18 and 55 years (mean: 30.64 +/- 8.59 years) and 18 postlingual adults (10 males, 8 females) with bilateral CIs ranging in age between 19 and 59 years (mean: 36.64 +/- 16.59 years) were included in the current study. Data Collection and Analysis: Hearing thresholds, word recognition scores (WRS), and GIN test were conducted for each participant. Two parameters of GIN test were determined: the GIN threshold and total percentage score (TPS). Mann Whitney U test was used to test the significance of the differences between the groups in terms of GIN threshold, WRS, and TPS. Results: CI group showed significantly (p < 0.001) poorer performance in terms of WRS than normal hearing group. However there were no significant differences in WRS between groups which were divided according to the implanted ear, gender, CI type, and sound processor strategies. The mean GIN threshold was 3.33 +/- 1.2 msec, whereas it was 9.56 +/- 3.49 msec in CI users. Moreover the mean value of TPS was 90.77% in the normal group and 47.22% in the CI group. These differences between the two groups were also found statistically significant (p < 0.001). Conclusions: Our results show that CI users do not discriminate GIN as well as normal-hearing individuals, although their hearing levels with CIs are very close to normal hearing limits at all frequencies.
Keywords: cochlear implants; speech perception; temporal resolution; RECOGNITION; FREQUENCY; AMPLITUDE; DEFICITS